Why we are losing the war on gun violence in the United States - Crandall, Marie (Springer, 2021)
1. Scope of firearm injuries in the United States -- 2. Gun Violence, Structural Violence, and Social Justice -- 3. Data on gun violence: what do we know and how do we know it?- 4. Unintentional firearm injuries in children -- 5. School Shootings: Creating Safer Schools -- 6. Intimate partner violence, gun violence, and human rights in the United States -- 7. Mental illness and gun violence -- 8. The need for safety and beliefs about guns -- 9. Understanding the political divide in gun policy support -- 10. The second amendment and the war on guns -- 11. The history of gun law and the second amendment in the United States -- 12. Public health approach to gun violence: "remove the gun handle" -- 13. Combatting gun violence in Newark, New Jersey -- 14. The impact of policy and law enforcement strategies on reducing gun violence in America -- 15. Gun buyback programs in the United States -- 16. Hospital-based violence prevention programs: From the ground up -- 17. Looking at the Second Amendment from the Tenth: Early experiences with a state gun violence research center -- 18. Youth Gun Violence Prevention Organizing -- 19. Smart guns don't kill people -- 20. Reducing the incidence and impact of gun violence through community engagement -- 21. Gun violence and barriers to reparation in the United States: Scars of Survival.